Frutescone O from Baeckea frutescens Blocked TLR4-Mediated Myd88/NF-κB and MAPK Signaling Pathways in LPS Induced RAW264.7 Macrophages - Lin, Xiaobing; Zhang, Junhan; Fan, Decai; Hou, Jiqin; Wang, Hao; Zhu, Lin; Tian, Ruina; An, Xiaofei; Yan, Ming (Frontiers in pharmacology, 2021)
Frutescone O was isolated from the aerial parts of Baeckea frutescens L., which was commonly used as a folk medicinal material for treating anti-inflammatory disease in South East Asia. This study aimed to investigate the anti-inflammatory activity and related signaling cascade of Frutescone O (Fru) in LPS induced RAW264.7 cells. The anti-inflammation activity of Frutescone O was determined according to the inhibitory effects on the secretion of nitric oxide (NO), expression of inducible NO synthase, and pro-inflammatory cytokines. The regulation of Myeloid differentiation factor 88 (Myd88), inhibition of NF-κB, and MAPK pathways were further investigated for molecular mechanisms. Fru significantly decreased the expression of iNOS and the production of NO in LPS-stimulated RAW264.7 cells. It also dose-dependently suppressed LPS induced expression of IL-1β, IL-6, and TNF-α. Furthermore, Fru remarkably inhibited the upregulation of NF-κB (p50) expression in the nucleus and the phosphorylation ratio of p38, JNK, ERK, and Myd88 signaling protein. The molecular docking and cellular thermal shift assay (CETSA) results indicated that Fru participated in a robust and stable interaction with the active site of TLR4-MD2. Thus, Fru suppressed the LPS induced inflammation in RAW264.7 cells by blocking the TLR4 mediated signal transduction through the NF-κB and MAPK signaling pathways and inhibiting the Myd88 and iNOS expression.